METODE DETEKSI TERUMBU KARANG DENGAN MENGGUNAKAN DATA SATELIT SPOT DAN PENGUKURAN SPEKTROFOTOMETER STUDI KASUS: PERAIRAN PANTAI RINGGUNG, KABUPATEN PESAWARAN - Arief, Muchlisin (Institut Teknologi Sepuluh Nopember, 2013)
Coral reefs are one of the spectacular ecosystems. These ecosystem provides good sand services, including protection from tropical storms, reef fisheries, opportunities for tourism and development of new pharmaceuticals. Coral reefs are marine resource that are to environmental changes (changes in water quality). it is very important to identify its status and monitor the changes of coralreef areas very often. Therefore, it is necessary to identify and monitor status changes as often as possible. This information is critical for conservation and sustainable development. This study focused on the identification of coral reefs by combining spectral information obtained from direct measurements in the field with the information band spectral remote sensing satellite SPOT. Based on the experiments, the correlation function which has the biggest correlation coefficient is a function obtained between the summation of the band (band1+band3) with the sum of spectral (spectral1 + spectral3). Based on the analsis, the methode/algorithm has been developed can identify/detect the shallow coral reefs/coral reefs-1 (depth of less than 1 meter) and not superficial coral reef/coral reefs-2 (depth of greater than 1 meters). Processing results show that Coral reefs-2 are found along the beach of Ringgung, while based on the calculation, around of the Tegal island there are 49 ha coral reefs-1, and 116 ha of Coral reefs-2, and around sandbar/sand arising surface water (area is 320 m²), the area coral reefs-1 are 12.38 ha and coral reef-2 in the area of approximately 42 ha.